Literature Review on the Implementation of Integrated Learning in Bireuen 4 Primary School - Kiki Fajariani (STMIK Indonesia Banda Aceh, 2024)
Integrated learning has become a prominent approach in elementary education, aiming to provide students with a holistic understanding of various subjects. This literature review examines the implementation of integrated learning at SD 4 Bireuen. The findings suggest that integrated learning positively impacts students' understanding of learning materials and fosters interdisciplinary skills development. However, challenges such as insufficient teacher training and support hinder its effective implementation. The role of school principals is crucial in facilitating integrated learning practices. Despite its potential benefits, concerted efforts from various stakeholders are necessary to overcome implementation challenges and enhance the effectiveness of integrated learning at SD 4 Bireuen.